2018
DOI: 10.1007/s00441-017-2759-9
|View full text |Cite
|
Sign up to set email alerts
|

The LRRK2 signalling system

Abstract: The LRRK2 gene is a major contributor to genetic risk for Parkinson’s disease and understanding the biology of the leucine-rich repeat kinase 2 (LRRK2, the protein product of this gene) is an important goal in Parkinson’s research. LRRK2 is a multi-domain, multi-activity enzyme and has been implicated in a wide range of signalling events within the cell. Because of the complexities of the signal transduction pathways in which LRRK2 is involved, it has been challenging to generate a clear idea as to how mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…LRRK2 encodes a 286-kDa protein with multiple functional domains; among the various mutations in LRRK2 , pathogenic mutations are primarily concentrated in the Ras of complex proteins (ROC) and the C-terminal of ROC (COR) domains, as well as in the kinase domain (G2019S and I2020T) ( Cookson, 2010 ). Since the discovery of the association between LRRK2 mutations and Parkinson’s disease, LRRK2 has been implicated in a variety of cellular functions, indicating that it is a multifunctional protein ( Drolet et al, 2011 ; Martin et al, 2014a ; Mata et al, 2006 ; Price et al, 2018 ; Wallings et al, 2015 ). In particular, LRRK2 has been implicated in the regulation of protein synthesis in Drosophila and in induced pluripotent stem cell (iPSC)-derived human neurons ( Imai et al, 2008 ; Martin et al, 2014b , 2014c ; Taymans et al, 2015 ); however, no specific disease-related translational target has yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…LRRK2 encodes a 286-kDa protein with multiple functional domains; among the various mutations in LRRK2 , pathogenic mutations are primarily concentrated in the Ras of complex proteins (ROC) and the C-terminal of ROC (COR) domains, as well as in the kinase domain (G2019S and I2020T) ( Cookson, 2010 ). Since the discovery of the association between LRRK2 mutations and Parkinson’s disease, LRRK2 has been implicated in a variety of cellular functions, indicating that it is a multifunctional protein ( Drolet et al, 2011 ; Martin et al, 2014a ; Mata et al, 2006 ; Price et al, 2018 ; Wallings et al, 2015 ). In particular, LRRK2 has been implicated in the regulation of protein synthesis in Drosophila and in induced pluripotent stem cell (iPSC)-derived human neurons ( Imai et al, 2008 ; Martin et al, 2014b , 2014c ; Taymans et al, 2015 ); however, no specific disease-related translational target has yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms linking LRRK2 to disease at a protein level have, as noted above, been the centre of much attention since 2004 (Alessi & Sammler, 2018). While a great deal of progress has been made, in particular with regard to the impact of coding variants on enzymatic function in the context of Parkinson's disease, there is still a level of divergence between the molecular consequences of different mutations (Price et al 2018). This may represent an underlying diversity in the pathways that link LRRK2 mutations to nigral degeneration; however, without a clearer understanding of the immediate signalling events surrounding LRRK2 it is also possible that the relevant molecular readouts for LRRK2 mutations have not yet been identified.…”
Section: Figure 4 Lrrk2 the Roco Kinases And Signal Transductionmentioning
confidence: 99%
“…The most frequent variation, affecting position 2019, results in an amino acid exchange from glycine to serine (G2019S) within a highly conserved DYG (aspartic acid/D, tyrosine/Y, glycine/G; or DFG [aspartic acid/D, phenylalanine/F, glycine/G] in most other kinases) motif in direct proximity to the activation loop of the kinase activity (Cookson, ; Kachergus et al., ; Mata, Wedemeyer, Farrer, Taylor, & Gallo, ). By today, several studies have reported that LRRK2 G2019S increases the kinase activity of the protein (first demonstrated by Jaleel et al., ; reviewed by Price and colleagues (Price, Manzoni, Cookson, & Lewis, )), while the effect of the I2020T variant (affecting the adjacent C‐terminal amino acid) on LRRK2 kinase activity has been discussed controversially (Gloeckner et al., ; Jaleel et al., ). Variants within or close to the ROC/COR domains (e.g.…”
Section: The Role Of Lrrk2 In the Pathogenesis Of Parkinson's Diseasementioning
confidence: 99%